Application of a dispersive solid‐phase extraction method using an amino‐based silica‐coated nanomagnetic sorbent for the trace quantification of chlorophenoxyacetic acids in water samples. Issue 17 (26th July 2017) - Ghambarian, Mahnaz; Behbahani, Mohammad; Esrafili, Ali; Sobhi, Hamid Reza
Abstract: Herein, an amino‐based silica‐coated nanomagnetic sorbent was applied for the effective extraction of two chlorophenoxyacetic acids (2‐methyl‐4‐chlorophenoxyacetic acid and 2, 4‐dichlorophenoxyacetic acid) from various water samples. The sorbent was successfully synthesized and subsequently characterized by scanning electron microscopy, X‐ray diffraction, and Fourier‐transform infrared spectroscopy. The analytes were extracted by the sorbent mainly through ionic interactions. Once the extraction of analytes was completed, they were desorbed from the sorbent and detected by high‐performance liquid chromatography with ultraviolet detection. A number of factors affecting the extraction and desorption of the analytes were investigated in detail and the optimum conditions were established. Under the optimum conditions, the calibration curves were linear over the concentration range of 1–250, and based on a signal‐to‐noise ratio of 3, the method detection limits were determined to be 0.5 μg/L for both analytes. Additionally, a preconcentration factor of 314 was achieved for the analytes. The average relative recoveries obtained from the fortified water samples varied in the range of 91–108% with relative standard deviations of 2.9–8.3%. Finally, the method was determined to be robust and effective for environmental water analysis.